Isolated Effects of Indian Ocean Basin-Wide and El Niño–Southern Oscillation on Austral Winter Rainfall over South America - Mary T. Kayano; Wilmar L. Cerón; Rita V. Andreoli; Rodrigo A. F. Souza; Itamara P. Souza (Atmosphere, 2021)
Contrasting effects of the tropical Indian and Pacific Oceans on the atmospheric circulation and rainfall interannual variations over South America during southern winter are assessed considering the effects of the warm Indian Ocean basin-wide (IOBW) and El Niño (EN) events, and of the cold IOBW and La Niña events, which are represented by sea surface temperature-based indices. Analyses are undertaken using total and partial correlations. When the effects of the two warm events are isolated from each other, the contrasts between the associated rainfall anomalies in most of South America become accentuated. In particular, EN relates to anomalous wet conditions, and the warm IOBW event to opposite conditions in extensive areas of the 5° S–25° S band. These effects in the 5° S–15° S sector are due to the anomalous regional Hadley cells, with rising motions in this band for the EN and sinking motions for the warm IOBW event. Meanwhile, in subtropical South America, the opposite effects of the EN and warm IOBW seem to be due to the presence of anomalous anticyclone and cyclone and associated moisture transport, respectively. These opposite effects of the warm IOBW and EN events on the rainfall in part of central South America might explain the weak rainfall relation in this region to the El Niño–Southern Oscillation (ENSO). Our results emphasize the important role of the tropical Indian Ocean in the South American climate and environment during southern winter.